Characterization of a Monoclonal Antibody Specific for the Parasite Surface Antigen-2 of Leishmania major - "AR Khabiri; F Bagheri; SR Naddaf; M Assmar; A Hosseini Taghavi" (Tehran University of Medical Sciences, 2004)
The Leishmania major Parasite surface Antigen-2 (PSA-2) is a family of glycoinositol phospholipids anchored glycoprotoins expressed in both promastigotes and amastigotes. Promastigote PSA-2 comprises three polypeptides with approximate molecular weight of 96, 80 and 50 kDa. Amastigote express a distinct but closely PSA-2 polypeptide with molecular weight of 50 kDa. In this study fusion of SP2/0 myeloma cells with immunized mice spleenocytes infected with promastigotes of L. major intraperitoneally resulted to a clone of hybridoma producing a specific antibody that only reacts with L. major parasite surface antigen (PSA-2). This mAb showed no crossreactivity with either other Leishmania species including L. tropica, L. donovani and L. infantum or recombinant gp63. Western blot analysis of culture supernatant revealed multiple bands with molecular weight of 50, 58, 80 and 96 kDa only in L. major.